A Case Study of a Successful System: The Scottish Lighthouses from the 18th to the 21st Century. Issue 1 (13th September 2016) - Sillitto, Hillary
Abstract: In the late 18 th century, the period in which Robert Louis Stevenson's novel Kidnapped was set, up to 20% of the cargo in ships sailing round the Scottish coast was lost to shipwreck. This level of financial loss made the ship owners willing to pay for safety systems to reduce the risk to their investment. There followed an astonishing period of engineering and organisational innovation to deploy a complex socio technical system that has continually delivered value for over two centuries. The 100 or so lighthouses built by the Stevenson family, all of them still standing and most of them still operating, were engineering marvels in their own right. But even more marvellous in many ways was the socio technical system the Stevensons and the Northern Lighthouse Board built to operate the "lighthouse capability". The paper will show how all components of modern capability management were developed to exploit the technology in an enduring and continuously evolving system‐of‐systems that made the wild seas off Scotland relatively safe for seafarers. Of particular interest is the long term strategic planning across multiple lines of development: as the light houses were automated, the inevitable workforce reduction was achieved by retirement and redeployment, not by redundancies. This whole story is an excellent example of "through‐life capability management" of an "enduring system". The paper also shows that modern approaches to systems architecting can be generalised – and that all perspectives offered by modern architecting methods are needed – to describe a two‐century‐old system! The case study also demonstrates the need to describe a system‐of‐systems at multiple levels, and a method for doing this.